Evaluación de parámetros reproductivos. i.a a celo natural e i.a.t.f en bovinos para producción de carne.en el rancho verito. - Amaya Delgado, Valeria Carolina (Machala : Universidad Técnica de Machala, 2022)
Reproductive biotechnologies are currently widely used in several countries in order to improve genetics, reproductive potential and the prevention of sexually transmitted diseases that can affect the reproductive system. Artificial Insemination (AI) is a technique that has been used for several decades and was the first biotechnology to be applied, however, based on AI, more studies were carried out on reproduction programs. Years later, Fixed Time Artificial Insemination (FTAI) began to be applied, which turned out to be very beneficial, not only in the reproductive aspect, but also economically, it is for this reason that the present experimental work was carried out with the objective of comparing the percentage of pregnancy with traditional Artificial Insemination and Fixed-Time Artificial Insemination with cryopreserved semen in meat-producing cows, with the purpose of knowing the effectiveness of both methods. The experimental work was carried out at the Rancho Verito, belonging to the El Progreso Parish of the Pasaje Canton, where 90 females were subjected to insemination, 66 destined for traditional Artificial Insemination and 24 for Fixed Time Artificial Insemination. Statistical analysis was performed to determine if there are significant differences between the two treatments, for this, an analysis for one factor (ANOVA) was used for the variables studied and Chi-Square to determine the effectiveness of the two treatments. Of the 66 cows inseminated in the traditional way, only 45 achieved pregnancy, while of the 24 destined for Fixed Time Artificial Insemination, only 13 achieved pregnancy. The results obtained on the influence of the Body Condition Score on pregnancy rates were different in treatment 1 and 2. In treatment 1, the cows that became pregnant had a body condition score (BC) of 3.02 ± 0.05, while that, in the treatment, the body condition was 3.48 ± 0.10, which indicates a statistically significant difference. It is concluded that there is an effect of CC, both methods are effective, depending on the CC of each animal and which straw does not influence pregnancy rates. Regarding the cows that did not become pregnant, it was observed that there is no notable effect that has to do with the Body Condition Score, since in treatment 1 (AI) the body condition was from 3.05 to 3.47, while in treatment 2 it was from 3.42 to 4.04. On the other hand, when breed was analyzed as a possible influencing factor on the pregnancy rate, it was observed that there was no statistically significant difference. Regarding the number of calvings and age of the females subjected to inseminations, it was observed that there were no statistically significant differences in both pregnant and empty cows. It is concluded that, based on the results obtained in the investigation, the body condition is a determining factor in the pregnancy rate, and it was shown that the two methods are effective depending on the body condition of each animal and the straw used. It does not intervene in pregnancy rates.
Las biotecnologías reproductivas en la actualidad, son muy utilizadas en varios países con la finalidad de mejorar la genética, el potencial reproductivo y la prevención de enfermedades de trasmisión sexual que puedan afectar al aparato reproductor. La Inseminación Artificial (IA) es una técnica que ha sido utilizada desde hace varias décadas y fue la primera biotecnología en aplicarse, sin embargo, a partir de la IA se realizaron más estudios acerca de programas de reproducción. Años más tarde, se empieza a aplicar la Inseminación Artificial a Tiempo Fijo (IATF), la cual resultó ser muy beneficiosa, no solo en el aspecto reproductivo, sino también económico, es por esta razón, que el presente trabajo experimental se llevó a cabo con el objetivo de comparar el porcentaje de preñez con Inseminación Artificial tradicional e Inseminación Artificial a Tiempo Fijo con semen criopreservado en vacas productoras de carne, con el propósito de conocer la efectividad de ambos métodos. El trabajo experimental, se realizó en el Rancho Verito, perteneciente a la Parroquia El Progreso del Cantón Pasaje en donde 90 hembras fueron sometidas a inseminación, 66 destinadas para Inseminación Artificial tradicional y 24 para Inseminación Artificial Tiempo Fijo. Se realizó el análisis estadístico para determinar si existen diferencias significativas entre los dos tratamientos, para ello, se empleó un análisis para un factor (ANOVA) para las variables estudiadas y Chi-Cuadrado para determinar la efectividad de los dos tratamientos. De las 66 vacas inseminadas de forma tradicional, sólo 45 lograron la preñez, mientras que de las 24 destinadas para Inseminación Artificial a Tiempo Fijo, solo 13 alcanzaron la preñez. Los resultados obtenidos sobre la influencia del Body Condition Score en los porcentajes de preñez fueron diferentes en el tratamiento 1 y 2. En el tratamiento 1 las vacas que quedaron preñadas presentaban una condición corporal (CC) de 3,02 ± 0,05, mientras que, en el tratamiento, la condición corporal fue de 3,48 ± 0,10 lo que indica una diferencia estadística significativa. Se concluye que sí existe un efecto de la CC, ambos métodos son efectivos, dependiendo de la CC de cada animal y que pajuela no influye en los porcentajes de preñez. Con respecto a las vacas que no quedaron preñadas, se observó que no hay un efecto notable que tenga que ver con el Body Condition Score, ya que en el tratamiento 1(IA) la condición corporal fue de 3,05 a 3,47, mientras que en el tratamiento 2 fue de 3,42 a 4,04. Por otro lado, cuando se analizó a la raza como posible factor influyente sobre el porcentaje de preñez, se observó que no hubo una diferencia estadística significativa. Con respecto al número de pariciones y edad de las hembras sometidas a las inseminaciones, se observó que no hubo diferencias estadísticas significativas tanto en vacas preñadas como vacías. Se concluye, que, en base a los resultados obtenidos en la investigación, la condición corporal si es un factor determinante en el porcentaje de preñez, y se demostró que los dos métodos son efectivos dependiendo de la condición corporal de cada animal y la pajuela utilizada no interviene en las tasas de preñez.
Keywords: INSEMINACIÓN ARTIFICIAL; SINCRONIZACIÓN; ARTIFICIAL A TIEMPO FIJO; ESTRO